Pre-service Teachers’ Perceptions on Governmental Suggested English Curriculum in Rural Areas (2021)
The analysis of different perceptions allows us to build a general viewpoint to find common factors on a specific topic. This study focuses on pre-service teachers’ perceptions regarding the implementation and scope of the Suggested English Curriculum (SEC) in rural areas of Boyacá, Colombia. A qualitative case study was conducted through narrative interviews, open-ended questionnaires, and a focus group. Several points of view were collected and classified into three categories explored from a narrow perspective to generate a broader view of the object of the study along with its respective exploration and analysis. Overall, pre-service teachers perceive it is difficult to achieve most of the SEC objectives in rural areas, given its characteristics and the high expectations from the Colombian Ministry of National Education (MEN due to its acronym in Spanish). Finally, the authors explore pedagogical implications and determine the path for further research.